2022
DOI: 10.7759/cureus.31780
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Analysis of Bone Graft Treated With Pasteurization or Cryotherapy Using Liquid Nitrogen: A Study Using Sheep Bone Model

Abstract: Osteosarcoma is a common primary malignancy of the bone. Osteosarcoma prognosis improves tremendously when chemotherapy is given in adjunct to surgical intervention. Limb reconstruction with sterilized autologous bone graft stabilized by orthopaedics implants has become a choice of treatment, but the biomechanical property of the bone treated with such sterilization method is a point of concern as a graft with inferior biomechanical property might lead to graft failure. This study compares the biomechanical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
0
0
Order By: Relevance
“…From a biomechanical and biological perspective, many previous studies have revealed the superiority of liquid nitrogen compared to the freezing method [14,[23][24][25]. A study discovered that autografts treated with liquid nitrogen freezing may result in better osteoinduction outcomes than those treated with extracorporeal irradiation (ECIR) [26].…”
Section: Original Articlementioning
confidence: 99%
“…From a biomechanical and biological perspective, many previous studies have revealed the superiority of liquid nitrogen compared to the freezing method [14,[23][24][25]. A study discovered that autografts treated with liquid nitrogen freezing may result in better osteoinduction outcomes than those treated with extracorporeal irradiation (ECIR) [26].…”
Section: Original Articlementioning
confidence: 99%